2002
DOI: 10.1111/j.1478-4408.2002.tb00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of additives on the fabric stiffness and colour depth of viscose printed with a guar gum thickener and a reactive dye

Abstract: The effect of additives in a printing paste containing guar gum thickener and bireactive dye for cellulose printing was studied. The efficiency of the additives with respect to their chemical structure and concentration and the efficiency in combination with thickeners of different types (nonsubstituted, different degrees of carboxymethylation) and different concentrations (solid content) was investigated by assessing the fabric stiffness, colour depth, dye penetration, the viscosity and viscoelasticity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Therefore, it was necessary to evaluate the per cent of dye penetration in correlation with the sharpness of the colour and its levelness. Previous studies have shown that dye penetration depends on the composition of the print paste and the lack of penetration can result in unlevelness [26,27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was necessary to evaluate the per cent of dye penetration in correlation with the sharpness of the colour and its levelness. Previous studies have shown that dye penetration depends on the composition of the print paste and the lack of penetration can result in unlevelness [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that dye penetration depends on the composition of the print paste and the lack of penetration can result in unlevelness [26,27]. Therefore, it was necessary to evaluate the per cent of dye penetration in correlation with the sharpness of the colour and its levelness.…”
Section: Dye Penetration and Levelling Propertiesmentioning
confidence: 99%
“…It was reported that the combination of low substituted guar gums with bifunctional reactive dyes causes fabric stiffness, though printing of most monofunctional vinylsulphone reactive dyes with guar gums results in good printing quality and fabric handle. Fabric stiffness increases with guar gum thickener composed of high solid content, which decreases with an increase in the degree of carboxymethylation of the thickener 3, 4…”
Section: Introductionmentioning
confidence: 99%